Renal blood flow in malignant disease of the liver. Issue 6 (June 1972) - Kew, M. C.; Limbrick, Carol A.; Varma, R. R.; Sherlock, Sheila
Abstract : Although functional renal failure has been reported in patients with malignant disease of the liver, renal haemodynamics and function have not been investigated. Renal and intrarenal blood flow was measured using the 133 Xenon washout technique and creatinine clearances by the standard method in 14 patients with a variety of primary and secondary tumours of the liver in the absence of cirrhosis and without evidence of renal disease. In 11 patients renal and outer cortical blood flow was reduced and this was sometimes accompanied by a reduction in glomerular filtration rate. The pattern of renal circulatory changes was similar to that seen in renal dysfunction associated with hepatic cirrhosis. Possible causes of these disturbances and their significance in relation to the aetiology of functional renal failure in liver disease are discussed.